Vegetable Perspectives and 2008 Outlook - John J. VanSickle (EDIS, 2008)
FE-708, a 3-page fact sheet by John J. VanSickle, characterizes the current vegetable production industry — demand, supply, international trade, regulatory issues, and short- and long-term outlooks. Published by the UF Department of Food and Resource Economics, February 2008.